Mengatasi Limbah Plastik: Peran Edukasi dan Ecobrick di Desa Penjalin - Azka Syariful Anam; Husnu Marya Ulfa; Wahyu Fatihah Cindana Sakti (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Plastic waste is one of the largest environmental issues globally, including in Penjalin Village. This study explores the role of environmental education and the use of ecobricks as innovative solutions to tackle plastic waste in rural communities. The research employs qualitative methods, including in-depth interviews and participatory observation, to analyze the impact of education on community awareness regarding plastic waste management. The findings indicate that effective education can enhance residents’ understanding and participation in utilizing ecobricks as an alternative waste management approach. Additionally, ecobricks have proven to be a sustainable method, reducing the volume of plastic waste while providing additional benefits such as increased creativity and community self-reliance. Thus, the combination of environmental education and ecobrick implementation can serve as an effective model for addressing plastic waste problems in other villages across Indonesia.